Osteonecrosis of the jaw among cancer patients in Denmark: risk and prognosis. Issue 11 (November 2022) - Gadgaard, N.R.; Olesen, T.B.; Svane, H.M.L.; Heide-Jørgensen, U.; Nørholt, S.E.; Ehrenstein, V.
Abstract: Osteonecrosis of the jaw (ONJ) is a serious complication of anti-resorptive therapy used in the treatment of multiple myeloma and cancerous bone metastases. In this study, patients with either multiple myeloma or solid tumours with a simultaneous or subsequent record of anti-resorptive treatment or bone metastases were identified using population-based medical registries. These patients were followed for the outcome of ONJ. Considering death as a competing risk, the cumulative incidence of ONJ was estimated, overall and by cancer site. Patients who developed ONJ were followed for the outcome of death overall and by several risk factors for ONJ. A total of 33, 975 cancer patients fulfilling the inclusion criteria were identified; 233 incidents of ONJ and a cumulative incidence of 1.9% (95% confidence interval 1.6–2.3%) over a maximum follow-up time of 7.5 years were observed. The 5-year cumulative incidence was 1.3% (95% confidence interval 1.2–1.6%) and varied by cancer site. There were 126 deaths among cancer patients with ONJ over a maximum follow-up time of 6.4 years, resulting in a 5-year mortality of 91% (95% confidence interval 81–97%). Mortality among patients with ONJ varied by cancer site, osteonecrosis stage, and by history of trauma to the mucosa.